2021
DOI: 10.1245/s10434-021-10233-5
|View full text |Cite
|
Sign up to set email alerts
|

Ureteroscopic Cryoablation for Patients with Upper Tract Urothelial Carcinoma of a Solitary Kidney: A Porcine Model and Our Pilot Clinical Experience

Abstract: Purpose To investigate the safety and efficacy of ureteroscopic cryoablation by a liquid-nitrogen system in a porcine model and for patients with upper tract urothelial carcinoma (UTUC) of a solitary kidney. Methods In the animal experiment, the right-sided ureter was frozen in nine pigs. Eight were randomly assigned to two different groups according to the freezing duration of 60 or 90 s. The other one was designed to receive a 10-min freeze. The treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“… 33 In our previous studies, we confirmed the safety of EBCA in the bladder in beagle and porcine models. 15 , 34 The EBCA‐TUR study was the first multicentre randomised clinical trial to evaluate endoscopic cryoablation in patients with bladder cancer. In addition, we conducted a pioneer study of ureteroscopic cryoablation in patients with upper tract urothelial carcinoma of a solitary kidney as the first worldwide attempt to use cryotherapy as a kidney‐sparing strategy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 33 In our previous studies, we confirmed the safety of EBCA in the bladder in beagle and porcine models. 15 , 34 The EBCA‐TUR study was the first multicentre randomised clinical trial to evaluate endoscopic cryoablation in patients with bladder cancer. In addition, we conducted a pioneer study of ureteroscopic cryoablation in patients with upper tract urothelial carcinoma of a solitary kidney as the first worldwide attempt to use cryotherapy as a kidney‐sparing strategy.…”
Section: Discussionmentioning
confidence: 99%
“…The feasibility and safety of EBCA have been confirmed in animal models and clinical trials. 15 , 16 Herein, we retrospectively analysed the prognosis of patients with bladder cancer who underwent cryoablation and compared it with that of patients who underwent transurethral resection of bladder tumour (TURBT). We present the first intensive investigation comparing the changes in peripheral blood lymphocyte subsets before and after cryoablation to reveal systemic immunomodulatory activities in patients with bladder cancer.…”
Section: Introductionmentioning
confidence: 99%
“…This process involves application of a liquid nitrogen probe on the residual tumor site, leading to formation of an ice ball and induction of necrosis/apoptosis from mucosa to lamina muscularis. This procedure shows early promise as an additional management technique to reduce r e c u r r e n c e f o l l o w i n g p r i m a r y l a s e r -b a s e d t u m o r destruction (67).…”
Section: Percutaneous Approachesmentioning
confidence: 99%
“…Percutaneous cryoablation has been widely used to treat malignancies in solid organs, such as the liver, kidney, and prostate. In terms of intraluminal tumors, endoscopic cryoablation has been introduced in recent years 7 . Only a few clinical trials have reported application of endoscopic cryoablation for precancerous gastrointestinal lesions and neoplasms, most of which were single‐arm or retrospective studies 8–11 .…”
Section: Introductionmentioning
confidence: 99%
“…In terms of intraluminal tumors, endoscopic cryoablation has been introduced in recent years. 7 Only a few clinical trials have reported application of endoscopic cryoablation for precancerous gastrointestinal lesions and neoplasms, most of which were single-arm or retrospective studies. [8][9][10][11] The inspiration for endoscopic balloon cryoablation (EBCA) was derived from the FIRE AND ICE study, which compared cryoballoon with radiofrequency ablation in paroxysmal atrial fibrillation.…”
Section: Introductionmentioning
confidence: 99%